A first-principles study of the switching mechanism in GeTe/InSbTe superlattices. Issue 11 (9th October 2020) - Ribaldone, Chiara; Dragoni, Daniele; Bernasconi, Marco
Abstract : Via density functional theory calculations, we devise a novel strain-engineered GeTe3 /In3 SbTe2 superlattice to reduce the power consumption of interfacial phase change memories. Abstract : Interfacial Phase Change Memories (iPCMs) based on (GeTe)2 /Sb2 Te3 superlattices have been proposed as an alternative candidate to conventional PCMs for the realization of memory devices with superior switching properties. The switching mechanism was proposed to involve a crystalline-to-crystalline structural transition associated with a rearrangement of the stacking sequence of the GeTe bilayers. Density functional theory (DFT) calculations showed that such rearrangement could be achieved by means of a two-step process with an activation barrier for the flipping of Ge and Te atoms which is sensitive to the biaxial strain acting on GeTe bilayers. Within this picture, strain-engineering of GeTe bilayers in the GeTe–chalcogenide superlattice can be exploited to further improve the iPCM switching performance. In this work, we study GeTe–InSbTe superlattices with different compositions by means of DFT, aiming at exploiting the large mismatch (3.8%) in the in-plane lattice parameter between GeTe and In3 SbTe2 to reduce the activation barrier for the switching with respect to the (GeTe)2 –Sb2 Te3 superlattice.